Egyptian predynastic anthropomorphic objects : a study of their function and significance in predynastic burial customs - Ordynat, Ryna (Archaeopress Publishing Ltd, 2018)
Anthropomorphic objects from the Egyptian Predynastic have been a topic of frequent study and debate, from the time they were first excavated until today. These objects, including human figurines, hippopotamus tusks, tag amulets and combs carved with the human image, continue to fascinate and perplex scholars today. Objects such as these form part of the extensive and distinctive iconographic imagery of Predynastic Egypt, and are often interpreted solely in the context of their symbolic or iconographic significance. The aim of this study is to examine these anthropomorphic objects in terms of their original context in order to determine what role they played in Predynastic burials - a useful method, as most of these objects are found in graves.